HnRNPR-mediated UPF3B mRNA splicing drives hepatocellular carcinoma metastasis - Hong Wang; Dong Qian; Jiabei Wang; Yao Liu; Wenguang Luo; Hongyan Zhang; Jingjing Cheng; Heng Li; Yang Wu; Wuhan Li; Jing Wang; Xia Yang; et al. (Journal of Advanced Research)
Introduction: Abnormal alternative splicing (AS) contributes to aggressive intrahepatic invasion and metastatic spread, leading to the high lethality of hepatocellular carcinoma (HCC). Objectives: This study aims to investigate the functional implications of UPF3B-S (a truncated oncogenic splice variant) in HCC metastasis. Methods: Basescope assay was performed to analyze the expression of UPF3B-S mRNA in tissues and cells. RNA immunoprecipitation, and in vitro and in vivo models were used to explore the role of UPF3B-S and the underlying mechanisms. Results: We show that splicing factor HnRNPR binds to the pre-mRNA of UPF3B via its RRM2 domain to generate an exon 8 exclusion truncated splice variant UPF3B-S. High expression of UPF3B-S is correlated with tumor metastasis and unfavorable overall survival in patients with HCC. The knockdown of UPF3B-S markedly suppresses the invasive and migratory capacities of HCC cells in vitro and in vivo. Mechanistically, UPF3B-S protein targets the 3′-UTR of CDH1 mRNA to enhance the degradation of CDH1 mRNA, which results in the downregulation of E-cadherin and the activation of epithelial–mesenchymal transition. Overexpression of UPF3B-S enhances the dephosphorylation of LATS1 and the nuclear accumulation of YAP1 to trigger the Hippo signaling pathway. Conclusion: Our findings suggest that HnRNPR-induced UPF3B-S promotes HCC invasion and metastasis by exhausting CDH1 mRNA and modulating YAP1-Hippo signaling. UPF3B-S could potentially serve as a promising biomarker for the clinical management of invasive HCC.